Research on the Failure of High-power Converter Module in Low Current Condition - YANG Guang; XIN Li; MA Bole; YANG Tao (Kongzhi Yu Xinxi Jishu)
It detailedly introduced the working characteristics of high-power converter module at low current, pursued theoretical analysis and research test, and summarized the factors resulting in the failure of IGBT, which provided some reference for reliability research of highpower converter.